Student ratings of instruction and student motivation: is there a connection? - Feit, Christopher R. (Kansas State University, 2014)
This study examined factors relates to student ratings of instruction and student levels of motivation. Data came from archival data of 386,195 classes of faculty and students who completed the Faculty Information Form (FIF), completed by the instructor, and the Student Ratings Diagnostic Form (SRDF) completed by the student from the Individual Development and Educational Assessment (IDEA) Center Student Ratings system. Descriptive statistics, correlation studies, analysis of variance (ANOVA), and pairwise comparisons were used to test the research hypotheses. Despite significant differences among student ratings of instruction and student motivation by course type, discipline, and student type, the amount of unknown variability in student ratings of instruction and student motivation is still very large. The findings from the study provide higher education institutions with information about differences between student ratings of instruction by institution type, course level, discipline, and course type as well as the impact of student motivation on student ratings of instruction.
Keywords: Student ratings of instruction; Student motivation; Teaching effectiveness; Educational Administration (0514); Educational evaluation (0443)